EVALUATION OF TECHNOLOGY AND ENGINEERING VOCATIONAL SCHOOL STUDENTS IMPLEMENTATION: SYSTEMIC LITERATURE REVIEW - Endah Sri Wahyuni; Riyan Arthur; Soeprijanto (Jurnal Pensil : Pendidikan Teknik Sipil, 2023)
Implementation of Field Work Practice (FWP) for Vocational High School (VHS) students is one of the programs planned as a means for students to improve competence in both soft skills and hard skills, besides that by carrying out FWP students get learning and training bythe world of work. Every student supervisor or teacher has difficulty evaluating the results of street vendors, due to the lack of references obtained by student supervisors in implementing the street vendors program at VHS. This study aims to identify and analyze various approaches and evaluation models that have been used in the implementation of street vendors in VHS students. This research method uses a systematic literature review (SLR) with a descriptive explanatory type of research to gain a comprehensive understanding of the evaluation of the street vendors program implementation. This study found 50 articles on the topic of street vendors from various disciplines, but 15 research articles that were appropriate to the topic of Technology and Engineering came from various literary sources or based on the database found on Google Scholar. This study produced three evaluation models, namely the Context, Input, Process, and Product (CIPP) model with 15 articles, the discrepancy model with 3 articles, and the goal-oriented model with 2 articles. The contribution of this research is expected to increase understanding of the evaluation of the implementation of the street vendors program for VHS students and to lay a strong basis for the development of better evaluations in the future.